2005
DOI: 10.1111/j.1523-1755.2005.00426.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential distribution of the vasopressin V2 receptor along the rat nephron during renal ontogeny and maturation

Abstract: Expression of V(2)R is first detectable in the late embryonic stage of rat ontogeny starting from day E18 and gradually increasing with kidney maturation. In the adult kidney, V(2)R is differentially distributed in the various nephron segments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
24
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 33 publications
(38 reference statements)
5
24
3
Order By: Relevance
“…Medullary and cortical TAL, macula densa and post-macula segment, distal convolutions, CCD and MCD epithelia, and a subset of type A intercalated cells of the three species expressed V 2 R mRNA to distinct degrees of intensity, but with no major interspecies differences. Localization of V 2 R mRNA to these epithelia likely reflected sites of receptor biosynthesis, since parallel immunohistochemistry from this and previous work has provided comparable results, and functional studies have, in part, indicated regional heterogeneity in the renal response to AVP (20,35), immunohistochemistry (30,39), or in situ hybridization (32). We have extended the information on overall V 2 R mRNA distribution and its celltype assignment by analyzing mouse and human kidneys.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Medullary and cortical TAL, macula densa and post-macula segment, distal convolutions, CCD and MCD epithelia, and a subset of type A intercalated cells of the three species expressed V 2 R mRNA to distinct degrees of intensity, but with no major interspecies differences. Localization of V 2 R mRNA to these epithelia likely reflected sites of receptor biosynthesis, since parallel immunohistochemistry from this and previous work has provided comparable results, and functional studies have, in part, indicated regional heterogeneity in the renal response to AVP (20,35), immunohistochemistry (30,39), or in situ hybridization (32). We have extended the information on overall V 2 R mRNA distribution and its celltype assignment by analyzing mouse and human kidneys.…”
Section: Discussionmentioning
confidence: 94%
“…Previous work has presented information on V 2 R distribution across several mammalian species, but results have in part been inconclusive, and information on cell-type-specific localization of V 2 R biosynthesis is scarce (9,30,32,39,47). These studies showed solid V 2 R expression in the CD, with some reference to regional differences in intensity believed to reflect AVPinduced effects on the stimulation/insertion of AQP-2 and urea transporter(s) (4,28,36).…”
mentioning
confidence: 82%
See 2 more Smart Citations
“…Arginine vasopressin (AVP) plays a central role in the mechanisms regulating blood pressure by stimulating the contraction of vascular smooth muscle cells and water reabsorption in the kidney [1][2][3][4][5][6][7]. Importantly, AVP acts as a growth factor inducing hypertrophy and cell growth in a variety of cell types [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%